PERAN KEPALA SEKOLAH DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM - Zaeni, Rezi Ahmad; Mustofa, Khabib; Cholid, Nur; Saputra, Ibnu Alwan (Institut Agama Islam Syubbanul Wathon Magelang, 2025)
This study aims to explore the role of the principal in developing the Islamic Religious Education (PAI) curriculum in schools. The main focus of this study is to understand how the principal leads and manages the development of a curriculum that is in accordance with the needs of effective religious education for students. The method used in this study is qualitative research with a library research approach, which prioritizes data collection through literature studies, journals, books, and documents that are relevant to the topic being studied. This approach was chosen to gain a deep understanding of the role of the principal in developing the PAI curriculum and the challenges faced in its implementation. The results of the study show that the principal has a very important role in designing, implementing, and evaluating the PAI curriculum. The principal functions as a leader who directs the curriculum development team, facilitates training for PAI teachers, and ensures that the curriculum implemented can meet applicable education standards and is relevant to current developments. In addition, the principal also has the responsibility to create an environment that supports quality religious learning and inspires students. The challenges faced include limited resources, lack of training for PAI teachers, and limited access to more modern and contextual curriculum references.